Development of the lubricant for side-mounted rail flange lubricators for traction rolling stock - D. V. Glazunov (Вестник Научно-исследовательского института железнодорожного транспорта)
Specificity of operating conditions of the rolling stock defines a number of requirements for lubricants intended for the wheel-rail tribosystem. Lubricants are used for “wheel — rail” contact, the aggregate state of which varies from liquid to solid. When evaluating the lubrication properties of these materials, a significant number of factors must be taken into account, in particular, influence of the environment, method of application, condition of the rail surface. The paper discusses the main operational requirements for lubricants operating in a wheel-rail tribosystem. Temperature ranges of the lubricants used for the “wheel — rail” contact on the railway network of the Russian Federation are given. As a result of the research, it was determined that none of the materials used for lubrication of the wheel-rail system satisfies the operating temperature conditions of the traction rolling stock.  To solve this problem a lubricant was developed and tested in an industrial environment at the Rostov State University of Railway Transport. Its lubricant composition allows to significantly expand the temperature range of the lubricant. Complex of experimental studies and method of orthogonal central composite plan of the 2nd order established the optimum values of the thickness of the working shell of the 0.846 mm lubricating rod and the 50.411 % percentage of plastic lubricant, allowing to extend the temperature range of lubricant rods and, in particular, completely eliminate the lubricant flow to achieve a temperature of 126.034 °C. Proposed composition of the lubricant was tested on a freight electric locomotive of the VL80T series, equipped with non-power lubricators, under the conditions of the Bataysk — Likhaya section of the North Caucasus Railway. Intensity of wear of the wheel flanges of the traction rolling stock lubricated by the proposed material, compared with the intensity of wear of the wheel flanges without the use of lubrication systems is reduced by 2 times.